Design and Development of a Decision Support System Using the SMART Method for Extracurricular Selection at the Singosari Delitua Education Foundation - Sitepu, Raynald; Mursyida, Lativa; Delianti, Vera Irma; Samala, Agariadne Dwinggo; Sinaga, Lotar Mateus (Cattleya Darmaya Fortuna, 2024)
This research aims to apply the SMART method (Simple Multi-Attribute Rating Technique) as a System Decision Support (SPK) in selecting activities extracurricular for students at the Singosari Education Foundation Delitua. The SMART method is applied to analyze criteria such as physical condition, medical history, interests, talents, and achievements, ensuring that students are matched with the most suitable extracurricular activities. Data collection was carried out through interviews and observations, followed by system design and testing. The research findings demonstrate that the SMART method successfully optimizes the decision-making process, enhances efficiency, and improves student satisfaction in extracurricular selection.